THE EFFECT OF TAXATION KNOWLEDGE, FISCUS SERVICES AND TAXATION SANCTIONS ON THE IMPLEMENTATION OF TAX AMNESTY PROGRAMS WITH TAXATION SOCIALIZATION AS MODERATING VARIABLES IN TAX OFFICE (KPP PRATAMA) MEDAN POLONIA - Saragih, Jendri Sunandar (Asosiasi Dosen Akuntansi Indonesia, 2020)
The purpose of this study was to examine and analyse the effect of tax knowledge, tax authorities and tax sanctions on the simultaneous and partial implementation of the tax amnesty program at the Medan Polonia Tax Office. This study also examines the moderating effect of taxation socialization in the relationship of tax knowledge, tax authorities, and tax sanctions with the implementation of the Tax Amnesty program at Medan Polonia Tax Office. This type of research is causal research. The population in this study were all Medan Polonia Taxpayers who followed the Tax Amnesty program. Samples were selected using the Slovin method so that 100 respondents were obtained. Data is processed using Smart PLS. The results of this study indicate that the simultaneous variables of tax knowledge, tax authorities and tax sanctions affect the implementation of the Medan Polonia Tax Office?s tax amnesty program. Partially, tax knowledge, tax authorities and tax sanctions variables have a significant effect on the implementation of the Medan Polonia Tax Office?s Tax Amnesty program. Variable tax socialization only moderates tax knowledge to the implementation of tax amnesty.